Carcinogenesis of the upper gastrointestinal tract induced by N-methyl-N '-nitro-nitrosoguanidine and reflux of duodenal contents in the rat - Naresse, Luiz Eduardo [UNESP]; Kobayasi, Shoiti [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (Acta Cirúrgica Brasileira, 2009)
Purpose: To investigate the combined effects of reflux of duodenal contents through the pylorus and treatment with N-methyl-N'-nitro-nitrosoguanidine ( MNNG) on the development of lesions in the glandular stomach, at the gastrojejunal anastomosis and in the forestomach of rats. Methods: Eighty Male Wistar rats were divided into 4 groups: G1: MNNG + Reflux, G2: Reflux, G3: MNNG and G4: Gastrostomy. MNNG was given in the drinking water ( 100 mg/ml) for 12 weeks and then two groups ( G1 and G2) were submitted to a gastrojejunal anastomosis followed by section of the afferent loop and suture of both stumps to allow reflux of duodenal contents through the pylorus. The animals were sacrificed 18 and 36 weeks after surgery. The lesions obtained in the antral mucosa, at the gastrojejunal anastomosis and in the forestomach were analysed histologically. Results: Duodenal reflux induced proliferative lesions at both glandular and squamous mucosa of the stomach. In the antrum, adenomatous hyperplasia (AH) was observed in 20% and 50% of the animals at the 18(th) and 36(th) weeks respectively. Aditionally 85% of the animals presented AH at the gastrojejunal anastomosis and 60% developed squamous hyperplasia at the squamous portion of the stomach. MNNG treatment plus duodenal reflux enhanced the development of malignant tumors at both glandular and squamous mucosa, since there were 30% of antral adenocarcinomas and 45% of squamous carcinomas at the 18th week and the frequency of these malignant tumors rose to 50% in the antrum and 65% in the squamous mucosa at the 36th week. Conclusion: The reflux of duodenal contents through the pylorus enhanced the development of proliferative lesions, benign and malignant, in the glandular stomach and in the forestomach of rats.

OBJETIVO: Investigar os efeitos do refluxo duodenogástrico e sua interação com o cancerígeno químico N-methil-N'-nitro-nitrosoguanidina (MNNG) no desenvolvimento de lesões no estômago glandular, anastomose gastrojejunal e no estômago escamoso do rato. MÉTODOS: Foram utilizados 80 ratos Wistar divididos em 4 grupos: G1: MNNG + Refluxo, G2: Refluxo, G3: MNNG e G 4: Gastrostomia. O MNNG foi oferecido na água de beber (100mg/ml) por 12 semanas. A seguir foi feita anastomose gastrojejunal na porção glandular do estômago nos grupos G1 e G2, com secção da alça aferente junto ao estômago e sutura de ambos os cotos para permitir o refluxo do conteúdo duodenal para o estômago pelo piloro. Os animais foram sacrificados 18 e 36 semanas após a cirurgia. As lesões identificadas foram submetidas à exame histopatológico. RESULTADOS: O refluxo duodenogástrico levou ao desenvolvimento de lesões proliferativas no estômago glandular e na porção escamosa. No antro, hiperplasia adenomatosa (HA) foi diagnosticada em 20 e 50% dos animais (G2) na 18ª e 36ª semanas, respectivamente. Na anastomose gastrojejunal 85% dos animais (G2) apresentaram HA e 60% apresentaram hiperplasia escamosa no estômago escamoso, na 36ª semana. No grupo MNNG+Refluxo foram identificados na 18ª semana, 30% adenocarcinomas no antro e 45% carcinomas escamosos. A freqüência destas lesões malignas aumentou, respectivamente, para 50% e 65% na 36ª semana. CONCLUSÃO: O refluxo duodenogástrico potencializou o desenvolvimento de lesões proliferativas benignas e malignas no estômago glandular e em sua porção escamosa, no rato.
Carcinogênese do trato gastrointestinal alto induzida pelo N-methyl-N'-nitro-nitrosoguanidina e pelo refluxo duodenogástrico no rato
Keywords: Upper Gastrointestinal Tract; Duodenogastric Reflux; Animal Experimentation; Rats